Corporate identity vs. corporate image in the eyes of professionals: an interview-based study - Wąsikiewicz-Firlej, Emilia (Scripta Neophilologica Posnaniensia, 2019)
Contrary to subsequent studies focused on the construction of corporate identity, this article aims to examine the stakeholder’s perception of corporate identity projected to the public through language and visual manifestations on corporate “About us” pages. A qualitative, data-driven approach has been taken in the study. The results, based on data collected from in-depth, semi-structured interviews with twenty professionals, demonstrate the interviewees’ deep scepticism towards corporate narrations, which are interpreted as persuasive and serving corporate ends. Thus, online projections of corporate identities do always match actual images held by stakeholders. The interviewees have emerged as critical readers of corporate communications and active constructors of corporate image.